The Effectiveness of Differentiated Learning Through Providing Structured Assignments in Algebraic Form Operational Materials Reviewed from the Learning Achievements and Learning Motivation of Class VII Students - Sudiara, I Ketut; Sugiman Sugiman (International Journal of Educational Technology and Society, 2024)
This research aims to describe how the effectiveness of differentiated learning strategies through giving structured assignments on class VII students' algebraic operations material in terms of: (1) student learning achievement, (2) student learning motivation, and (3) student learning achievement and student learning motivation simultaneously. This research is a quasi-experimental research with a pretest and posttest non-equivalent group design. This research is quantitative research with experimental methods, This type of research is a quasi-experiment, a pretest-posttest nonequivalent control group design. The subjects in this research were 66 students, divided into two classes, namely 33 experimental class students and 33 control class students. The data collection technique for student learning achievement uses a multiple choice test with 20 questions and an essay with 2 questions, while for data on student learning motivation uses a questionnaire in the form of a questionnaire with 25 questions. Data analysis used two sample t-test analysis using statistical formulas and the SPSS 27 for Windows program. The results showed that the differentiated learning strategy through structured assignments on the material of the operation of algebraic forms of seventh grade students was 1) ineffective in terms of student learning achievement, 2) effective in terms of student learning motivation, and 3) effective in terms of student learning achievement and student learning motivation simultaneously.